Development of E-Health Information Technology During The Covid-19 - T Fidowaty; E Engwin; A A Noprisanti; Maulidina Aisyah (International Journal of Education, Information Technology, and Others, 2021)
This study aims to analyze how the development of E-Health Information Technology during the Covid-19 period. The research method used in this research is a case study method with a qualitative approach. Researchers used data collection techniques through observation, interviews, and documentation studies. This study's results indicate that the analysis of the development of information and communication technology on the E-Health system in the Alodokter.com health information service includes selecting doctors as partners for providing web-based health information and mobile apps. Moreover, socialization services are very beneficial for the community (patients). This research concludes that the development of E-Health Information Technology for the Covid-19 Period in the process of selecting doctors, disseminating information services, and the benefits of using Alodokter.com will be a continuous and better process in the future in the aspects of Information and Communication services that take place in use Alodokter.com.